2020
DOI: 10.3389/fpls.2020.585212
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cyclophilins: Multifaceted Proteins With Versatile Roles

Abstract: Cyclophilins constitute a family of ubiquitous proteins that bind cyclosporin A (CsA), an immunosuppressant drug. Several of these proteins possess peptidyl-prolyl cis-trans isomerase (PPIase) activity that catalyzes the cis-trans isomerization of the peptide bond preceding a proline residue, essential for correct folding of the proteins. Compared to prokaryotes and other eukaryotes studied until now, the cyclophilin gene families in plants exhibit considerable expansion. With few exceptions, the role of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 301 publications
(331 reference statements)
0
38
0
Order By: Relevance
“…Estimation of the PPIase proteins by immunoblotting is, nonetheless, required to understand the molecular basis of this observation. Since protection by cyclophilins and FKBPs against stress-induced damage to the cell is attributed to their PPIase activity and/or chaperone functions 80 , further biochemical characterization of these proteins in Penicillium is imperative to elucidate their precise mechanism of action. Although expression of other PPIases was not observed at the stages studied, their role in specific developmental processes and adaptation to other stresses cannot be ruled out as previous studies have demonstrated the role of these genes in the regulation of several developmental process 80 .…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the PPIase proteins by immunoblotting is, nonetheless, required to understand the molecular basis of this observation. Since protection by cyclophilins and FKBPs against stress-induced damage to the cell is attributed to their PPIase activity and/or chaperone functions 80 , further biochemical characterization of these proteins in Penicillium is imperative to elucidate their precise mechanism of action. Although expression of other PPIases was not observed at the stages studied, their role in specific developmental processes and adaptation to other stresses cannot be ruled out as previous studies have demonstrated the role of these genes in the regulation of several developmental process 80 .…”
Section: Discussionmentioning
confidence: 99%
“…PPIases are the class of stress-responsive proteins of the immunophilin family. It catalyzes various biological functions such as transcription regulation, protein folding and degradation, signal transduction, and reactive oxygen species (ROS) regulation, cell wall strengthening to cope with stress conditions [66][67][68][69][70]. A plethora of recent reports indicate that PPIases are critical resistance/tolerance factors against various biotic and abiotic stresses in crops [69,[71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…PPIases, also called immunophilins, are a family of ubiquitous proteins with multiple functionalities in plants [50]. Two subfamilies are known: cyclophilins (CYPs) and FK506 binding proteins (FKBPs).…”
Section: Global Proteome Analysis After 2xh Candidates For Priming An...mentioning
confidence: 99%